EVALUATION OF THE POSITIONAL QUALITY THROUGH THE POSTPROCESSING OF RAW GNSS DATA FROM A SMARTPHONE VIA DIFFERENT SATELLITE POSITIONING METHODS - Gomes, Allan; Krueger, Claudia Pereira (Boletim de Ciências Geodésicas, 2020)
Since the introduction of the Android 7 in August 2016, it has become possible to use raw data collected by GNSS sensors present in some Android smartphones and tablets. Therefore, it became possible, for the first time, to perform the post-processing of the data, which means to obtain coordinates that are more accurate than usual, from meters to decimeters. In addition, among the technological innovations in the context of positioning via smartphones, it is mentioned the use of modern GNSS sensors, like the one used by Xiaomi Mi 8, which was the first smartphone to integrate a dual-frequency GNSS sensor. In this research, data collection campaigns were carried out in static mode to evaluate the quality of geodetic coordinates obtained from Mi 8. Using freely available applications that store raw data in files in RINEX format, the data was post-processed with different positioning methods and with different software, including the freely available IBGE-PPP online service in Brazil. The results of this research show that it is possible to obtain geodetic coordinates with an accuracy at decimeter order, which indicates that the methodology can be used in some engineering applications.